ZMIANY WARUNKÓW TERMICZNYCH W PILE W LATACH 1971–2020 - MATUSZAK, ZUZANNA (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2020)
The paper focuses on changes of the thermal conditions in Piła in 1971–2020. In the study, daily data were obtained from the Institute of Meteorology and Water Management – the National Research Institute, to analyze the variability of the annual, seasonal and monthly average air temperature, develop a thermal classification and determine the variability of the start dates and the length of 6 thermal seasons. The analysis showed an increase in the average air temperature for all of the time intervals. The consequence of the progressive warming was the increasingly frequent occurrence of months, seasons and years with thermal conditions above the norm for the entire studied period. The research also showed statistically significant changes in the dates of the beginning of the spring, summer, autumn and early winter, with the highest trend in the autumn.